Penerapan Metode Enzimatis pada Pembuatan Gula Cair dengan Lama Sakarifikasi dan Konsentrasi Substrat yang Berbeda - Ayu Wiji Lestari; Iffah Muflihati (Talenta Publisher (Universitas Sumatera Utara), 2026)
Liquid sugar is utilized in the food and beverage industry due to its advantages of being non-crystallizing, practicable, soluble, and visually improved appearance. The horned banana, in particular, contain high levels of carbohydrates and starch, having the potential development into liquid sugar through enzymatic hydrolysis using α-amylase and glucoamylase enzymes. The aim of this study to determine the treatment resulting in the highest yield of reducing sugars and review the effect of long saccharification and substrate concentration of horned banana starch, on the physicochemical of liquid sugar. The horned bananas was gelatinized a temperature of 75°C using starch concentrates of 15%, 20%, and 25%, liquefied for 6 and 8 hours, and vaporized for 24 hours at 60°C. These results prove that the longer the duration of saccharification and the higher the starch substrate concentrate, the high yield, reducing sugar content, dextrose equivalent, and °Brix value. The optimal treatment was 8 hours of saccharification and a 25% starch substrate. This produced a yield of 59.89%, a reducing sugar content of 25.64%, a DE (dextrose equivalent) of 16.77%, and a TPT (°Brix) of 29.87%.